Identification of genes that interact with the sina gene in Drosophila eye development. - Carthew, R W (1994)
The sina gene encodes a nuclear protein that is required for the correct development of R7 photoreceptor cells in the Drosophila eye. We conducted a genetic screen for mutations that reduce the activity of sina and found mutations that define nine genes whose products may be required for normal sina activity. Three of these genes also appear to be essential for signaling by the Sevenless-Ras pathway in R7 cells, of which one gene corresponds to the rolled locus (rl). The rl gene is known to encode a mitogen-activated protein kinase necessary for signaling by Ras. These results suggest that the products of these three genes may participate in a signaling pathway involving both Ras and Sina, possibly by functionally linking these two proteins.